A Sufictic Evaluation Of The Characters Of The Mesnevy Gul u Bulbul By Fazli 16th Century Poet - Demirel, H. Gamze (Selcuk Univ, Inst Turkish Studies, 2007)
In this mesnevy, the love between Gul u Bulbul is taken up in a sufistic manner. Each of the characters in the mesnevy has been chosen from the ingredients of nature. In this story, in which loves -that are shaped around the rose- and the dimensions of them (exaltation, humiliation etc.) are expressed, the rose represents a character of having personality concern. The nightingale's love towards the rose and its mood as a result of this love determines the main direction of the episodes.
Keywords: Classical Turkish Literature; Rose; Nightingale; Love; Sufism